Industrial Organization of Financial Systems and Strategic Use of Relationship Banking - Yafeh, Yishay; Yosha, Oved (Review of Finance, 2001)
Abstract Using standard Industrial Organization tools, we analyze the relation between competition in arm's length financial markets and the prevalence of close bank-firms ties. We show how the degree of competition between financial intermediaries affects the intensity of relationships between banks and client firms, and explore the idea that investment in bank-firm relationships can be used strategically by incumbent multi-product (universal) banks to limit competition in arm's length markets. The analysis implies that reforms designed to facilitate entry of new intermediaries may actually induce incumbent banks to increase investment in relationship banking, so that regulatory entry barriers are replaced by entry barriers created endogenously, namely, there is “path dependence” in the market structure of financial systems. This result suggests that increased (potential) competition in the financial services industry will not always destroy bank-firm relationships but, on the contrary, may actually strengthen them. JEL classification numbers: G21, L1